Accuracy of magnetic resonance imaging in the pre‐operative staging of rectal adenocarcinoma: Experience from a regional Australian cancer center. Issue 4 (26th November 2012) - White, Rohen; Ung, Kim Ann; Mathlum, Maitham
Abstract Aim Selection of the optimal treatment pathway in patients with rectal adenocarcinoma relies on accurate locoregional staging. This study aims to assess the accuracy of staging with magnetic resonance imaging (MRI) and in particular, its accuracy in differentiating patients with early stage disease from those with more advanced disease who benefit from a different treatment approach. Methods Patients who were staged with MRI and received surgery as the first line of treatment for biopsy‐proven adenocarcinoma of the rectum were identified. Comparison was made between the clinical stage on MRI and the pathological stage of the surgical specimen. The sensitivity, specificity and overall accuracy of MRI was assessed. Results In all, 58 eligible patients were identified. In 31% of patients, the extent of disease was underrepresented on preoperative MRI. Sensitivity, specificity and overall accuracy of anorectal MRI in detecting stage II/III disease status in this cohort was 59, 71 and 62%, respectively. Conclusion MRI underestimated the pathological stage in many patients in this series who may have benefited from the addition of neoadjuvant radiotherapy to their management. This study supports further refinement of preoperative staging and demonstrates that impressive results from highly controlled settings may be difficult to reproduce in community practice.